Diagnosis dan Tatalaksana Sindrom Kardiorenal - Evelyne M. Jirajaya; Octavianus R. H. Umboh; Frans E. N. Wantania (Universitas Sam Ratulangi, 2023)
Heart disease and kidney disease are interconnected and have become a global health problem. There is a close relationship between the heart and kidneys, where kidney failure can cause heart injury and conversely heart damage can lead to worsening of kidney function. This condition is called cardiorenal syndrome (CRS). This study aimed to discuss the diagnosis and treatment of cardiorenal syndrome. This was a literature review study using three database resources, namely ClinicalKey, Pubmed, and Google Scholar, to search articles related to inclusion and exclusion criteria. The results obtained 13 articles; 10 articles discussing the diagnosis of CRS and 10 articles discussing the treatment of CRS. The diagnosis of CRS in both acute and chronic conditions could be seen through multi-organ biomarkers from urine and blood samples, imaging, and in assessing the volume status of CRS. Treatment with rapid volume reduction might help to relieve symptoms. Diuretics were the primary agents for correcting volume overload on CRS. There were other alternative treatments such as neurohormonal modulation inhibitors, inotropes, vasodilators/vasopressin, RAAS inhibitors, cardiac device therapy, and others. In conclusion, diagnosis of CRS is confirmed by using multiorgan biomarkers, imaging, and volume status, and its management is performed by correcting volume overload with diuretics or alternatives. Keywords: cardiorenal syndrome; diagnosis; treatment Abstrak: Penyakit jantung dan penyakit ginjal saling berhubungan dan telah menjadi masalah dalam dunia kesehatan. Terdapat hubungan erat antara organ jantung dan ginjal, dimana gagal ginjal dapat memperburuk cedera jantung dan sebaliknya kerusakan jantung dapat mendorong perburukan fungsi ginjal. Keadaan tersebut disebut dengan sindrom kardiorenal (SKR). Penelitian ini bertujuan untuk mengetahui diagnosis dan tatalaksana SKR. Jenis penelitian ini ialah suatu literature review. Pencarian data menggunakan tiga sumber database yaitu ClinicalKey, Pubmed, dan Google Scholar sesuai dengan kriteria inklusi dan eksklusi. Hasil penelitian mendapatkan 13 artikel yang dilakukan review. Terdapat 10 artikel yang membahas diagnosis SKR dan terdapat 10 artikel yang membahas tatalaksana SKR. Penegakan diagnosis pada SKR baik dalam kondisi akut dan kronis dapat dilihat melalui biomarker multi-organ dari sampel urin maupun darah, pencitraan (imaging), dan pada penilaian status volume SKR. Tatalaksana dengan pengurangan volume secara cepat dapat membantu meringankan gejala. Diuretik merupakan agen primer untuk mengoreksi kelebihan volume SKR. Terdapat tatalaksana alternatif lainnya seperti penghambat modulasi neurohormonal, inotropik, vasodilator/vasopressin, penghambat RAAS, terapi perangkat jantung, dan lainnya. Simpulan penelitian ini ialah diagnosis SKR ditegakkan melalui biomarker multiorgan, pencitraan dan penilaian status volume. Tatalaksana dengan pengurangan volume menggunakan diuretik atau alternatif. Kata kunci: sindrom kardiorenal; diagnosis; tatalaksana